An inquiry from user’s perspective into the furniture with open-source recipes in the context of do-ityourself theme - KOÇ SAĞLAM, CEREN (My University, 2020)
The frontiers of today’s world which we know and perceive of and which is defined as the modern changed along with globalization and digitalization. In this regard, new concepts which come into play by virtue of the influence exerted by changing paradigms and fringe experiences on human being’s understanding of consumption and production and the existence of these new concepts on the agenda shape the theoretical and practical literature in relation to design. Along with fast growth of consumption and change in consumption culture and the accessibility of information and expansion of information base, the human being began to be interested either in the production by himself/herself of the objects which he/she desired to own or owned or in the improvement of such objects by adding something from himself/herself. This interest launched the advancement of the ‘Do-It-Yourself’ movement whose tracks we could see on the perspective of humanity’s historical process concerning the practice of doing. In the context of this movement, recipes including information on how human beings will do the objects which they are interested in doing are shared as open source on web pages developed under ‘do-it-yourself’ theme. As a response to this approach, human being as the consumer started to produce what he/she needed and to consume what he/she produced. The relationship of the user, who took a passive and/or an active part in traditional furniture design, with the furniture of today’s changing understanding of consumption was addressed through do-it-yourself theme. For this study which was performed on furniture produced with do-it-yourself theme, an experimental research was configured on the basis of user’s experience. In the study, an internet site which had a wide network was selected from among internet sites replete with uploads allowing consumption through production and designated as open source, equipped with do-it-yourself theme, current in terms of recognition, supported by well-known institutions and agencies and/or associated with well-known institutions and agencies and endowed with an experience of more than a decade at least. Three recipes posted on the internet site which was called as Instructables and categorized under do-it-yourself theme were selected and utilized by authors of this study who assumed the role of users. The only precondition for selected recipes which would be practically applied through this study was for them to be for furniture. Authors selected and utilized furniture which they needed solely in the context of their own life routines. In this process of practice, authors themselves experienced the do-it-yourself theme on a one-on-one basis directly through the furniture which they themselves produced. Besides this practice, evaluations on conventional furniture and user roles were presented in conjunction with the topic. Through theoretical framework and experimental research under this study, answers to the following questions were sought: Can a different definition of user be offered under do-it-yourself theme? How is the dialog between user, producer, designer, design and design recipe from user perspective? Can anybody produce furniture? What are its differences from conventional furniture production and consumption processes? Is there any difference between do-it-yourself furniture and mass-produced or special fabrication furniture made by furniture manufacturing sector? In conclusion, it was observed that do-it-yourself theme would be an area of experience in consumption culture for the user, user’s roles became vaguer, and there would be different dynamics of production processes and accessibility of information. In the consumption culture, the user is not just the one who purchases the final product and uses it, but he/she is in a position to experience the production process fully and the design process partially and to exert influence on these processes. The user is able to reshape and contribute to the recipe of furniture which is supposed to be emerging as the final product and consumed by himself/herself. Thus, the user adds new dynamics to the design process as he/she is involved in processes under the current system of do-it-yourself theme. In this conjunction, it was found that furniture produced in the context of this theme could not be characterized as the final product, rather, as the furniture in constant motion.
Keywords: Furniture; furniture design; user; do it yourself; design recipe